Enhanced selective cytotoxicity of doxorubicin to breast cancer cells by methoxypolyethylene glycol conjugation via a novel beta-thiopropanamide linker - Wiwat Supasena (2020)
© 2020 Elsevier Ltd Doxorubicin (DOX) is a chemotherapeutic agent that suffers from severe adverse effects due to non-selective cell cytotoxicity. This study designs a novel beta-thiopropanamide linker (A) which conjugates DOX with methoxypolyethylene glycol (mPEG) to sustain systemic drug release, and to promote cancer enzyme-responsiveness and cell selectivity. The mPEG-DOX conjugate with the beta-thiopropanamide linker (P-A-DOX) conjugate was synthesized using thiol-functionalized methoxypolyethylene glycol and acrylic acid to establish the beta-thiopropanamide linkage with DOX, with the mPEG-DOX (P-DOX) conjugate as the control. The conjugates were structurally characterized by NMR, chemical assay, transmission electron microscopy and dynamic light scattering technique. The in vitro hydrolytic stability as a function of pH and cytotoxicity tests (MDA-MB-231 and MCF-7 breast cancer cells vs MCF-10A noncancerous cells) were performed. The P-A-DOX and P-DOX conjugates can self-assemble into nanoparticles. The P-A-DOX and P-DOX conjugates exhibited sustained drug release and improved physicochemical stability under physiological pHs. Their cancer cell cytotoxicity and selectivity progressed in the following order: P-A-DOX > P-DOX > DOX. The P-A-DOX conjugate with the beta-thiopropanamide linker is a selective DOX nanodelivery system for breast cancer treatment.